Changes in activity and structure of jaw muscles in Parkinson's disease model rats. (19th January 2013) - Nakamura, S.; Kawai, N.; Ohnuki, Y.; Saeki, Y.; Korfage, J. A. M.; Langenbach, G. E. J.; Kitayama, T.; Watanabe, M.; Sano, R.; Tanne, K.; Tanaka, E.
Summary: Parkinson's disease (PD), a major neurological disease, is characterised by a marked loss of dopaminergic neurons in the substantia nigra. Patients with PD frequently show chewing and swallowing dysfunctions, but little is known about the characteristics of their stomatognathic functions. The purpose of this study was to evaluate the influence of PD on jaw muscle fibre and functions. PD model rats were made by means of the injection of 6‐hydroxydopamine (6‐OHDA) into the striatum of 8‐week‐old Sprague‐Dawley male rats. Five weeks after the injection, a radio‐telemetric device was implanted to record muscle activity continuously from the superficial masseter and anterior belly of digastric muscles. Muscle activity was recorded for 3 days and was evaluated by the total duration of muscle activity per day (duty time). After recording the muscle activities, jaw muscles were isolated for immunohistochemical and PCR analyses. In PD model rats, the following findings of the digastrics muscles verify that compared to the control group: (i) the higher duty time exceeding 5% of the peak activity level, (ii) the higher expression of the mRNA of myosin heavy chain type I, and (iii) the tendency for fast to slow fibre‐type transition. With respect to the masseter muscle, there were no significant differences in all analyses. In conclusion, PD leads to the changes in the jaw behaviours, resulting in a PD‐specific chewing and swallowing dysfunctions.